ANALYSIS OF THE PHENOMENON AND PSYCHOMETRICS OF MILITARY LEADERSHIP: FOREIGN EXPERIENCE - Mykolaichuk, Olena; Siroshtan, Oleksiy; Pampukha, Igor; Loza, Vitalii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Leadership in the Armed Forces not only determines the effectiveness of managerial decisions in complex and dynamic environments but also influences the level of trust, motivation, and readiness of military personnel to carry out assigned missions. It is based on a shared understanding of values, regulations, ethical standards, requirements, criteria, and parameters that define the effectiveness of leadership behavior. Exploring international experience contributes to identifying best practices that have demonstrated their effectiveness in various contexts and can be adapted to the transformational processes within the Armed Forces of Ukraine. The purpose of this study is to conduct a comparative analysis of models and psychometric tools of military leadership in the armed forces of the United States of America, the United Kingdom of Great Britain and Northern Ireland, the Federal Republic of Germany, the State of Israel, and the countries of the Middle East to identify key principles, structural elements, and practices for the formation of effective leadership that can be adapted to the conditions of transformation of the Armed Forces and the military education system in Ukraine. M e t h o d s . The following methods were applied in the course of the study: comparative analysis; content analysis of legal acts, official defense strategies, and military doctrines; systemic and interpretative analysis; and elements of case study methodology.R e s u l t s . The study involved a comprehensive analysis of approaches to military leadership development in the armed forces of partner nations and the Middle East. Key trends in the development of leadership in the military environment were identified, along with an overview of psychometric tools used to assess leadership attributes and competencies. Given that a significant portion of such tools is not publicly available, the study was primarily based on open-source materials.C o n c l u s i o n s . The integration of experience from partner countries and the Middle East contributes to the formation of new models that combine military discipline with high ethical responsibility, such as the democratically integrated models of military leadership in United States of America and the Federal Republic of Germany; Israel's Defense Forces unique leadership experience under constant external threat and high-intensity combat; the analysis of advantages and shortcomings of authoritarian leadership models in Middle Eastern countries shaped by cultural-religious factors, political regimes, or post-conflict transformation. In the context of full-scale armed aggression against Ukraine, the development of an effective corps of military leaders is a key factor in ensuring national resilience, invincibility, and the further security integration of the state into the international arena.
Keywords: military leadership, military management models, attributes, competencies, psychometric tools, international experience, military personnel, partner countries